Determination of the Optimal Business Development Strategy for Huawei Technologies Co., Ltd Based on Selected Strategic Analysis Tools - Bin Wu; Alexey Chernov (Communications of International Proceedings, 2022)
In the context of digitalization of different spheres of life business-processes, trends and tendencies evolve, basic business-models evolve as well. The revision of key aspects of development plays a more important role in the company’s survival on the market — the development and implementation of a new long-term strategy, taking into account the transformation of the market. In this regard international companies more actively use different tools and methods of strategic analysis. This paper contains the results of research on Huawei Technologies Co., Ltd company based on such tools as SWOT-analysis, ADL matrix and a multiparameter SPACE-matrix. The author formulated basic conclusions and recommendations regarding possible strategies of improving the competitiveness on the current market and the possibility of developing a new market by the company was considered.
Keywords: strategic analysis; strategy; business strategy; ADL; SPACE; SWOT; competitive advantages; Huawei Technologies Co.; Ltd